A Systematic Review of Mandibular Distraction Osteogenesis Versus Orthodontic Airway Plate for Airway Obstruction Treatment in Pierre Robin Sequence. (March 2022) - Abbas, Darren B.; Lavin, Christopher; Fahy, Evan J.; Choo, HyeRan; Truong, Mai Thy; Bruckman, Karl C.; Khosla, Rohit K.; Lorenz, H. Peter; Momeni, Arash; Wan, Derrick C.
Objective: Mandibular distraction osteogenesis (MDO) is frequently performed to address airway obstruction in patients with Pierre Robin sequence (PRS), though more recently the technique of orthodontic airway plating (OAP) has gained traction. We aimed to evaluate OAP compared to MDO for airway obstruction in PRS. Design: A systematic literature search across PubMed, Embase, and Google Scholar identified all studies published in English, which involved MDO or any form of OAP as treatments for PRS. All relevant articles were reviewed in detail and reported on, adhering to PRISMA guidelines. Main Outcome Measures: Airway (tracheostomy avoidance, decannulation rate), feeding (full oral feeding tolerance). Results: Literature search identified 970 articles, of which 42 MDO studies and 9 OAP studies met criteria for review. A total of 1159 individuals were treated with MDO, and 322 individuals were treated with OAP. Primary outcomes appear similar for MDO and OAP at face value; however, this must be interpreted with different pretreatment contexts in mind. Conclusions: Orthodontic airway plating may be considered for airway obstruction in PRS, as some airway-related and feeding-related outcomes appear similar with MDO, per existing evidence in the literature. However, since PRS severity differed between studies, OAP cannot be uniformly considered a replacement for MDO. Further research is required to more comprehensively assess these treatment modalities inclusive of metrics that allow for direct comparison.